Analysis of Pathogenic Bacteria in Ready-to-eat Fried Chicken in the Jember University Campus Area - Suswati, Enny; Supangat, Supangat; Rahmat, Indra Samudra; Mukarromah, Laylatul Fitriyah (Universitas Halu Oleo, 2022)
Poultry meat is a food that is widely consumed in various forms, but it is also a reservoir of bacteria. This study aims to isolate and identify the type of contaminant bacteria in fried chicken sold in the Jember University campus area. This research is a laboratory epidemiological survey research, in January - March 2021. 79 fried chicken samples came from 27 stalls along Jalan Kalimantan, Jalan Jawa, Jalan Riau and Jalan Mastrip Jember. Isolation and identification of bacteria using chromogenic media, namely Mannitol Salt Agar (MSA) and Salmonella Chromogenic Agar (SCA). The identification of bacteria based on the color of the growing bacterial colonies was then confirmed with API E 20 media. The results showed that 98.7 % of fried chicken samples contained at least 1 type of bacteria. The types of bacteria that contaminate fried chicken are Escherichia coli (98.8 %), Staphylococcus aureus (94.9 %), Salmonella typhimurium (26.5 %), Salmonella typhi (8.8 %), and Proteus spp. (2.5 %). Thus, consumers' proper hygiene and safety practices have been suggested as the main intervention and need to be followed up with regular surveys to assess behavioral changes and reduce knowledge gaps.Keywords: ready to eat, fried chicken, foodborne diseases